Barriers for identification and treatment of problem drinkers in primary care - Ainhoa Coloma-Carmona; José Luis Carballo; Sonia Tirado-González (Elsevier, 2017)
Objective: Due to the lack of studies in the Spanish population, this study aims to analyze the barriers perceived by health professionals from different Spanish health centers when attempting to identify and treat problem drinkers and the importance given to this aspect, as well as analyzing the possible differences as a function of the professionals' health teams. We also analyze the psychometric properties of the questionnaire used to assess these barriers. Method: The participants included 107 health professionals: 62.7% belonged to the medical team and 32.4% to the nursing team. After we had reviewed previous studies, collecting the main barriers referred to in them, participants completed an ad hoc questionnaire. Results: The main barriers found were the belief that patients will lie about their actual consumption and will not identify its negative consequences, and the belief that they will reject participating in an intervention for their alcohol consumption. No significant differences between doctors and nurses were found in any of the barriers assessed. The results provide empirical evidence of the reliability of the test for the assessment by both teams of professionals. Conclusions: Studies are needed to examine in greater depth these conclusions, extending the number of variables studied to determine a more complete profile of the health professionals who are reluctant to incorporate the assessment and treatment of problem drinkers in their consultation. This could help to improve the design of programs to facilitate and encourage its implementation in primary care.